Examining the Body through Technology: Age disputes and the UK border control system - Smith, Evan; Marmo, Marinella (Anti-Trafficking Review, 2013)
In an effort to ascertain whether certain migrants and refugees have been telling the ‘truth’ about their age, the UK border control system has, in the past, relied on the use of skeletal x- ray to estimate the applicant’s age, and in recent years has sought to use dental x-ray for the same purpose. However using x-ray for age assessment purposes has been criticised as inaccurate in providing a reasonable estimate of age and as an unnecessary medical risk, which infringes the human rights of the applicant. This is particularly pertinent in the case of children who are victims of trafficking and unaccompanied young people who may be vulnerable to exploitation, because if declared as children, they can access a higher level of care and protection under childcare law. The article argues that the deferment to the use of x-ray to reveal the ‘truth’ in age disputes is evidence that the border control system is more concerned with keeping ‘undesirable’ people out of the UK than observing the human rights of the vulnerable people who come into contact with the system.